2017
DOI: 10.1371/journal.pone.0178910
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E reduces obesity and related metabolic dysfunction in mice by targeting JAK-STAT5 signaling pathway

Abstract: Several members of cucurbitaceae family have been reported to regulate growth of cancer by interfering with STAT3 signaling. In the present study, we investigated the unique role and molecular mechanism of cucurbitacins (Cucs) in reducing symptoms of metabolic syndrome in mice. Cucurbitacin E (CuE) was found to reduce adipogenesis in murine adipocytes. CuE treatment diminished hypertrophy of adipocytes, visceral obesity and lipogenesis gene expression in diet induced mice model of metabolic syndrome (MetS). Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Our study was positively compared with the previous study associated with cucurbitacin and expression of PPARγ in skeletal muscle and adipose tissue. [18,21] In conclusion, our present findings suggest that administration of cucurbitacin shows authoritative antioxidant potential and elevated insulin secretion through signal transduction in rats. In addition, cucurbitacin also exerts antihyperglycemic effect by enhancing glucose uptake into skeletal muscle via PI3K-Akt signaling pathway.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our study was positively compared with the previous study associated with cucurbitacin and expression of PPARγ in skeletal muscle and adipose tissue. [18,21] In conclusion, our present findings suggest that administration of cucurbitacin shows authoritative antioxidant potential and elevated insulin secretion through signal transduction in rats. In addition, cucurbitacin also exerts antihyperglycemic effect by enhancing glucose uptake into skeletal muscle via PI3K-Akt signaling pathway.…”
Section: Discussionsupporting
confidence: 56%
“…[15] Further, the studies indicated that cucurbitacins has cytotoxic effects on various cancer cells, including bladder, pancreas, liver, mammary gland and blood. [16][17][18] In addition, the study further reported that cucurbitacins inhibit JAK-STAT signaling in various cancer cell lines. [19,20] Furthermore, the recent study showed inhibitory role of cucurbitacin on adipocytes in vitro.…”
Section: Banu World Journal Of Pharmaceutical Researchmentioning
confidence: 94%
“…Additionally, the extracellular signal-regulated kinase 1/2 (ERK1/2) is known to promote adipocyte differentiation and hypertrophy [10, 11]. Importantly, pharmacological treatment to reduce adipocyte hypertrophy has been shown to improve IR and resolve adipose inflammation [10, 12, 13]. Identifying factors contributing to these adipose tissue expansion and inflammatory signal pathways is important for managing obesity and associated metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that curcurbitacin I can inhibit STAT3 in SeAx cells and primary Sz cells [ 32 ]. Moreover, cucurbitacin B and E have been shown to inhibit STAT5 activation in other cell types [ 45 , 46 ]. To investigate the role of STAT3 and STAT5 activation in SeAx cells treated with cucurbitacin E and I, levels of total and phosphorylated protein were measured ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Van Kester et al [ 32 ] previously showed that STAT3 activation and total STAT3 levels are affected by cucurbitacin I treatment in Sz. Furthermore, several cucurbitacins have been shown to inhibit STAT5 activation in other diseases [ 45 , 46 ]. This is interesting, since it has been suggested that STAT5, not STAT3, has an important role in promoting survival in lymphoid tumors [ 60 ].…”
Section: Discussionmentioning
confidence: 99%